2018
DOI: 10.1177/2058460118772863
|View full text |Cite
|
Sign up to set email alerts
|

New patient-controlled abdominal compression method in radiography: radiation dose and image quality

Abstract: BackgroundThe radiation dose for patients can be reduced with many methods and one way is to use abdominal compression. In this study, the radiation dose and image quality for a new patient-controlled compression device were compared with conventional compression and compression in the prone position.PurposeTo compare radiation dose and image quality of patient-controlled compression compared with conventional and prone compression in general radiography.Material and MethodsAn experimental design with quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Both the patients and the radiographers believed that the conventional compression method was safer and resulted in a decreased radiation dose and increased image quality compared with the patient‐controlled compression. Swedish legislation prescribes that the radiation dose should be kept to an absolute minimum (Radiation Protection Act, ), and a previous study concluded that the two compression methods described here are similar with regard to radiation dose and image quality (Piippo‐Huotari et al, ). Balleyguier's study showed that compression was better with patient‐assisted compression, and image quality was equivalent compared with technologist‐assisted compression (Balleyguier et al, ).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Both the patients and the radiographers believed that the conventional compression method was safer and resulted in a decreased radiation dose and increased image quality compared with the patient‐controlled compression. Swedish legislation prescribes that the radiation dose should be kept to an absolute minimum (Radiation Protection Act, ), and a previous study concluded that the two compression methods described here are similar with regard to radiation dose and image quality (Piippo‐Huotari et al, ). Balleyguier's study showed that compression was better with patient‐assisted compression, and image quality was equivalent compared with technologist‐assisted compression (Balleyguier et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…It was tested in a previous study where we evaluated patient‐controlled compression compared with conventional compression. The study did not find any difference in radiation dose or image quality between the two methods (Piippo‐Huotari et al, ). It is, however, important to know the patients' and the radiographers' experiences of compression in general and of the new method specifically, to develop methods further and make compression devices as easy to use as possible.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations